Research on the Attitudes of the Elderly towards Interprofessional Cooperation and Collaborative Pharmacy Practices: Cross-sectional Study in Serbia - Ilić, Velibor O; Tasić, Ljiljana; Marinković, Valentina (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Population aging is taking place at the highest historical rates, while growing needs for healthcare by the elderly put added and immense pressure predominantly on the primary care. Higher level of interprofessional collaboration is expected to improve healthcare system performance and to provide adequate delivery of healthcare for the elderly. This was the main driver for implementing the interprofessional collaborative models by many countries. However, these models need to be patient-centered and more focused on “what matters” to patient. This study aims to identify the attitudes of the elderly people (65+) towards interprofessional collaboration (IPC), namely collaborative pharmacy practice (CPP). Methods: A cross-sectional study was carried out in Serbia from May 2017 to July 2017, taking place in five Geriatric Centers. A total of 187 men and women (average age 76.2 years), were interviewed using a structured questionnaire. Results: Respondents noted the insufficient visibility of the elderly and insufficient informing as the biggest problems faced by the elderly within the system of health and social care. The significant difference by gender and education was found in several questions. However, respondents believed that the efficiency of the healthcare system would significantly increase if there were closer cooperation and coordination between doctors, pharmacists and other healthcare workers. Conclusion: The lack of collaborative pharmacy practice represents a significant unused potential for improving healthcare for the elderly considerably, which under the conditions of limited resources may stipulate organizational changes or corrections.
Keywords: Cross-sectional survey; Collaborative practice; Healthcare; Attitudes; Elderly